Influence of cognitive processes on the intention to segregate solid waste, according to gender of university students - Perez Fon, Diana C. (2022)
The research aimed to determine the differences in the influence of cognitive processes on the intention to segregate solid waste between university women and men. The cognitive processes studied are explained using the theory of protection motivation as a basis. The study sample was 189 students from a public university, stratified into 97 women and 92 men. For inferential statistics, the normality test and simple linear regression analysis were used. The results indicate that there is a significant positive influence of cognitive processes on the intention to segregate. It was also evidenced that, although women show a greater influence, the difference with men is not significant. It is concluded that, although it is important to take into account the difference in the influence of the cognitive processes of women and men when designing segregation programs in universities; apparently, this difference between genders becomes less significant as people achieve more education.